Structural and optical study of Sm3+ doped Ca3(VO4)2 phosphors. (2022) - Chauhan, Vaibhav; Kumar Pandey, Prashant; Dixit, Prashant; Pandey, Praveen C.
Abstract: Herein, we report the preparation of Sm 3+ (0, 1, 4, and 5%) doped Ca3 (VO4 )2 phosphor by the combustion process. The XRD result ascertains the rhombohedral crystal structure with symmetry described by the space-group of R3c for all the samples. The crystallite size of the phosphors is in the range of 46.5 to 50 nm. Absorption analysis manifests that all samples have near UV absorption at 290 nm which is ascribed to the ligand to metal charge transfer band (CTB), formed as a consequence of electron transfer from O 2– to V 5+ in [VO4 ] 3- tetrahedral. The bandgap of the host phosphor is 3.70 eV and decreases after Sm 3+ doping. The decrease in the bandgap is because of the formation of the defect energy levels in the bandgap of the host. The FTIR analysis confirms all the infrared modes present in the phosphors. The PL analysis ascertains the occurrence of emission peaks for Sm 3+ doped Ca3 (VO4 )2 . These 4f-4f transition peaks are ascribed to 4 G5/2 to 6 HJ (J = 5/2, 7/2, 9/2, and 11/2) electronic transitions of Sm 3+ ions. The calculated lifetime of the 4 G5/2 energy level of Sm 3+ ion for 4% doped Ca3 (VO4 )2 is 0.66 ms. Here we have discussed the consequence of Sm 3+ doping on the structure and photoluminescence characteristics of the Ca3 (VO4 )2 phosphor. Thus, our analysis of Sm 3+ doped Ca3 (VO4 )2 phosphor ascertains that it has potential application in various optoelectronic devices such as LEDs and plasma panels.